An update on sexual function and dysfunction in women - Khajehei, M.; Doherty, M.; Tilley, Peter (SPRINGER WIEN, 2015)
Sexual function of women can be affected by many factors resulting in female sexual dysfunction (FSD). Sexual dysfunction is a common problem among women of all ages and has negative effects not only on their quality of lives but also on the sexual function and quality of life of their partners. It can also affect mental health of the entire family and society. Regarding the multidimensional nature of female sexual dysfunction and considering its consequences, this condition needs to be recognised in its early stages in order to prevent future consequences and impacts. This article discusses biopsychosocial aspect of female sexual function, classifications and risk factors of female sexual dysfunction and investigates current approaches to identify and treat this problem.